The Impact of Trust, Perceived Usefulness, and Perceived Values Mediated by Customer Satisfaction towards Repurchase Intention of Tokopedia and Shopee - Hendra Kuncoro; Benjamin Martin Wirawan (iBuss Management, 2023)
During the beginning of pandemic in 2020, the growth of e-commerce in Indonesia has flourished rapidly, resulting from the large number of people choosing to purchase goods and services through the comfort of their own house. One of Indonesia’s local e-commerce is Tokopedia. Tokopedia has been leading the e-commerce since 2011. However, their market share and success are competing against a foreign e-commerce namely Shopee, who has an outstanding growth in the e-commerce market for the last four years. Hence, this research will study the behavior of consumers and their factors to repurchase from two different e-commerce, which are required to analyze the most significant factors that have influence towards the satisfaction of consumers that resulted in repurchase intention behavior. The researchers will focus on finding out the influence of trust, perceived usefulness, and perceived value towards repurchase intention and the mediating role of customer satisfaction across Tokopedia and Shopee. This research uses simple random sampling and focuses on people who has recently used both Tokopedia and Shopee in the last 3 months. 211 valid respondents are gathered in this research and the data is processed through PLS-SEM. This research study the mediation effect of customer satisfaction towards that factors that are known to have influence towards customer repurchase intention. The result of this study will provide a strategic recommendation towards Tokopedia or other e-commerce to understand the driver of consumer behavior that might vary across e-commerce platforms. Keywords: e-commerce, Indonesia, repurchase intention, customer satisfaction, trust, perceived usefulness, perceived value.